The economic cost of ill health due to air pollution: Evidence from Greece - Maria Panteli; Sofia Delipalla (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2021)
Purpose: Air pollution and its adverse health effects result in an economic cost to society. Given that the burden of disease from air pollution is to a large extent preventable, estimation of the magnitude of its economic cost is important. We estimate the economic cost of the health impact from exposure to ground-level ozone, and ambient and household PM2.5 air pollution, as well as their joint effects, in Greece. Design/methodology/approach: We analyze the economic cost of the health impact from air pollution using the Cost-ofIllness (COI) as well as the Willingness to Pay (WTP) approach. Finding: Based on the COI approach, air pollution attributable diseases resulted in a total economic cost of exteuro1.27 billion in 2019, or 0.68 percent of GDP. Under the WTP approach, mortality cost is significantly higher. Research limitations/implications: In spite of some standard methodological limitations, giving a monetary value to the burden of disease from air pollution highlights the significance of curbing air pollution, providing at the same time guidance in prioritizing among various competing policy objectives. Air pollution abatement interventions can yield significant benefits for global health and the economy. Originality/value: To the best of our knowledge, this is the first study estimating direct and indirect costs of air pollution-attributable health consequences in Greece, using the most recent data for all specific-cause mortality and morbidity outcomes. Employing two alternative methodologies, COI and WTP, we provide a lower and an upper bound of the economic cost of air pollution, respectively. The COI estimates provide a financial measure of the potential gains (by age and gender) if air pollution were to be extensively mitigated. The WTP estimates are a starting point in a cost-benefit analysis evaluating certain environmental regulation policies. Our results and their policy implications could be a guide to other economies with similar characteristics and comparable air pollution levels with those in Greece.
Keywords: I18; Q51; Q53; 330; Air Pollution; HealthEffects; Economic Cost; Mortality and MorbidityCost; Healthcare Expenses; Greece